Determination of nutrition indices and their correlation with activity of lupus nephritis - Rabrenović, Violeta; Petrović, Milica; Rabrenović, Milorad; Rančić, Nemanja (Vojnosanitetski pregled, 2024)
Background/Aim. Lupus nephritis (LN), as an immuno-inflammatory kidney lesion and the most severe manifestation of systemic lupus erythematosus (SLE), is accompanied by a disorder of nutritional status of patients. The aim of our study was to determine the importance of parameters of nutritional status [nutritional risk index (NRI), prognostic nutritional index (PNI), and Controlling Nutritional Status (CONUT)] and their association with standard parameters of LN activity. Methods. The clinical study included a group of 92 participants: 67 patients with LN (34 patients had LN active disease – the LNa group, and 33 patients were in LN remission – the LNr group) and 25 healthy subjects in the control group. In addition to standard laboratory parameters and LN activity parameters, derived parameters were also determined: PNI = 10 × serum albumin value (g/dL) + 0.005 × total lymphocyte count/mm3; NRI = 1.519 × serum albumin value (g/dL) + 41.7 × present weight (kg)/usual body weight (defined as stable body weight for last six months) (kg); CONUT score = serum albumin value (g/dL) + total lymphocyte count/mm3 + total cholesterol level (mmol/L). Results. A statistically significant difference between all three groups was observed for the PNI (p = 0.001) and the CONUT score (p = 0.000), while there was no significant difference for NRI. In the LNa group, a statistically significant correlation was found for PNI in relation to albumin, complement C3 and C4, and a statistically significant negative correlation with the level of anti-double stranded (ds) DNA antibodies (Abs). NRI had a statistically significant correlation only with proteinuria in the LNa group. CONUT showed significant correlations with most of the parameters of disease activity: negative correlation with albumin and complement C3 (p = 0.000), and positive correlation with anti-dsDNA Abs (p = 0.002), Systemic Lupus Erythematosus Disease Activity Index/renal (SLEDAI/r), and proteinuria g/24 hrs (p = 0.000). Conclusion. A statistically significant difference was observed between the groups for the nutrition score CONUT and the PNI. Their correlation with standard parameters of active disease was significant for most parameters in the group of patients with LNa.